The Impact Of The Internet On Albanian Teenagers - Lila, Bukurie (European Scientific Journal, ESJ, 2016)
The aim of this study is to look at the social impact that the internet has on the teenagers of "Arben Broci" school in Tirana. The study looks at the activities that teenagers engage themselves in on the internet, the hours they spend there, and the social influence that these activities have on them. By interviewing 100 people of different ages, some of which were interviewed in the high school, “Arben Broci” in Tirana, we have gathered qualitative and quantitative data through the use of a questionnaire. After the study, we concluded that the internet has both positive as well as negative impacts on socially isolated adolescents. We have seen that adolescents engage themselves in online chats through which they exchange data and information with people they do not know. This puts them at risk. In majority of the cases, they meet people whom they do not know their motives. The risk of child exposure to pornography and exploitation has increased along with the rise in internet use. The global nature of the internet also increases the child’s risk of meeting a predator. According to Wolfe & Higgings (2008), more attention has been given to online solicitation of sex from children. The positive social impact of the internet is that it creates an environment where teens can seek information needed for educational purposes. The study concludes that parents, teachers, and the government must be aware of the social impact of the internet on the lives of adolescents. Therefore, they must work together to minimize the harmful impacts of the internet on socially isolated students.